2004
DOI: 10.1002/dys.278
|View full text |Cite
|
Sign up to set email alerts
|

Working memory: Its role in dyslexia and other specific learning difficulties

Abstract: This paper reports a study contrasting dyslexic children against a control group of children without special educational needs (SEN) and a group with varied SENs. Children's abilities were compared on tasks assessing phonological processing, visuo-spatial/motor coordination and executive/inhibitory functioning; being targeted for assessment based on theoretical proposals related to the working memory model. Primary and secondary school level children were tested: 21 assessed as dyslexic with no comorbid diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
195
2
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(225 citation statements)
references
References 29 publications
15
195
2
13
Order By: Relevance
“…Research on the relationship between DD and VSSP deficits has yielded mixed results. Although most studies have not found VSSP deficits in individuals with DD (Bacon, Parmentier, & Barr, 2013;Jeffries & Everatt, 2004;Kibby & Cohen, 2008;Schuchardt et al, 2008), others have suggested the presence of significant differences, with individuals with DD performing more poorly than TR (Menghini et al, 2011;Smith-Spark & Fisk, 2007). When visuospatial STM tasks involve CE demands, children with DD tend to exhibit more difficulties.…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 97%
See 3 more Smart Citations
“…Research on the relationship between DD and VSSP deficits has yielded mixed results. Although most studies have not found VSSP deficits in individuals with DD (Bacon, Parmentier, & Barr, 2013;Jeffries & Everatt, 2004;Kibby & Cohen, 2008;Schuchardt et al, 2008), others have suggested the presence of significant differences, with individuals with DD performing more poorly than TR (Menghini et al, 2011;Smith-Spark & Fisk, 2007). When visuospatial STM tasks involve CE demands, children with DD tend to exhibit more difficulties.…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 97%
“…Studies employing more specific measures have also reported that children with DD exhibit strong evidence of WM impairments, particularly in the PL and CE components (Jeffries & Everatt, 2004;Menghini, Finzi, Carlesimo, & Vicari, 2011;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: Working Memory Impairments In Developmental Dyslexiamentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, Reiter, Tucha, and Lange (2005) showed differences between children with and without dyslexia on visual working memory, just like Smith‐Spark and Fisk (2007) found adults with dyslexia to be impaired on visuospatial working memory. On the other hand, Jeffries and Everatt (2004) found no differences between children with and without dyslexia on visuospatial working memory tasks.…”
Section: Introductionmentioning
confidence: 97%